2005
DOI: 10.1038/sj.cdd.4401552
|View full text |Cite
|
Sign up to set email alerts
|

The permeability transition pore triggers Bax translocation to mitochondria during neuronal apoptosis

Abstract: Cerebellar granule neurons (CGNs) require depolarization for their survival in culture. When deprived of this stimulus, CGNs die via an intrinsic apoptotic cascade involving Bim induction, Bax translocation, cytochrome c release, and caspase-9 and -3 activation. Opening of the mitochondrial permeability transition pore (mPTP) is an early event during intrinsic apoptosis; however, the precise role of mPTP opening in neuronal apoptosis is presently unclear. Here, we show that mPTP opening acts as an initiating e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
66
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 43 publications
5
66
0
1
Order By: Relevance
“…This time frame is sufficient to elicit cytochrome c release 5,6 and BAX translocation to mitochondria. 27 Therefore, BAX translocation to mitochondria is not associated with a permeability transition, 45 although the decreased spare respiratory capacity ( Figure 3, Table 1) would be consistent with partial release of cytochrome c by outer membrane permeabilization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This time frame is sufficient to elicit cytochrome c release 5,6 and BAX translocation to mitochondria. 27 Therefore, BAX translocation to mitochondria is not associated with a permeability transition, 45 although the decreased spare respiratory capacity ( Figure 3, Table 1) would be consistent with partial release of cytochrome c by outer membrane permeabilization.…”
Section: Discussionmentioning
confidence: 99%
“…5,6,37,44 The mechanism of release, whether by activation of the permeability transition pore 6,45 or BAX association with mitochondria 27 is unclear. In the present study, no significant change in oligomycin-insensitive proton leak was evident over 1-5 h of K þ /serum deprivation ( Figure 3, Table 1), despite the ncreasing number of cells showing signs of apoptosis during this period (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…PTP may also help Bax pore-forming activity (Narita et al, 1998): it has been reported that whenever PTP is open, Bax recruitment from the cytosol to the mitochondrial membrane is facilitated (Precht et al, 2005); in addition, PTP facilitates the acquisition of the correct poreforming supra-molecular assembly of membrane-bound Bax (De Giorgi et al, 2002).…”
Section: Cooperation With the Mitochondrial Permeability Transition Porementioning
confidence: 99%
“…23 Recent evidence has shown that bax apoptotic activity is regulated by translocation of cytoplasmic bax to the mitochondria under apoptotic stimuli. 12,24,25 This translocation is dependent on the conformational change in the C terminus of bax protein by dephosphorylation of serine at position 184 26 and possibly threonine at position 182. 24 The phosphorylation and dephosphorylation of bax have been suggested to be regulated by PKC zeta 27 and PP2A, 28 respectively.…”
Section: Introductionmentioning
confidence: 99%
“…12,24,25 This translocation is dependent on the conformational change in the C terminus of bax protein by dephosphorylation of serine at position 184 26 and possibly threonine at position 182. 24 The phosphorylation and dephosphorylation of bax have been suggested to be regulated by PKC zeta 27 and PP2A, 28 respectively. The objective of this study was to generate a nonviral gene therapy vector with significant and selective activity in tumor cells.…”
Section: Introductionmentioning
confidence: 99%